Campo Grande on the route from Marcha para Oeste (Revista de História Regional, 2009)
The Estado Novo (1937-1945) was a period of significant change for Mato Grosso. The program of colonization entitled Marcha para Oeste, announced by President Vargas, in 1937, renewed not only the prospects of development for the state, but at the same time opened the possibility of the arrival of new social actors, represented, on one side, for entrepreneurs / investors and, in addition, for new urban characters, like employees, players, prostitutes, etc.. Generally speaking, both could mean threat to the dominant local elites. Accordingly, this article intends to discuss the reordenamentos, occurring at the time, within those elites at the same time if empenhavam in developing and / or strengthening of the positive images on the state, in order to, definitely, delete the "stigma of barbarism" that the traditionally characterized.